A Review on Enhancement of Friction Stir Welding (FSW) Settings for Microstructural Assessment and Mechanical Characteristics on Aluminium 6082 and Copper Joints - B. Lalit Kumar; Dr. Vikash Gadpale (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Aluminium and its alloys are the major material that is used in today’s world. Aluminium alloys are alloys in which Aluminium (Al) is the predominant metal. The typical alloying elements are copper, magnesium, manganese, silicon and zinc. Among the various available Al alloys Al6082 exhibits the properties like low weight, High strength to mass ratio, Weldability etc. Copper and its alloys are widely used in industrial applications due to their excellent electrical and thermal conductivities, good strength, and corrosion and fatigue resistances. The joints of dissimilar materials are widely used in industrial applications due to their technical and beneficial advantages. Aluminium and copper are two common metals in the electric power industry due to unique performances such as higher electrical conductivity, heat conductivity, corrosion resistance and mechanical properties. Friction Stir Welding (FSW) is a relatively new solid-state joining process. It was initially applied to aluminium alloys. In this study, the effect of different process parameters in dissimilar FSW of Al6082 alloy and copper and mechanical behaviour of the same are studied by conducting hardness, bending and tensile tests. Process optimization was done using Taguchi technique along with ANOVA analysis
Keywords: Al 6082; Dissimilar Materials; Friction Stir Welding; Taguchi Technique; ANOVA